New solution of diffusion–advection equation for cosmic-ray transport using ultradistributions - Rocca, Mario Carlos (2015)
In this paper we exactly solve the diffusion–advection equation (DAE) for cosmic-ray transport. For such a purpose we use the Theory of Ultradistributions of J. Sebastiao e Silva, to give a general solution for the DAE. From the ensuing solution, we obtain several approximations as limiting cases of various situations of physical and astrophysical interest. One of them involves Solar cosmic-rays’ diffusion.